Inspædia: [Almost] Everything About Simplicity, Playfulness and Inspiration - Maldonado, Paulo (2020)
The aim of this paper is to disclose the new research developments and the results from the systematization of experience and user interaction with the Inspædia (a new web knowledge “Agora”), to inspire a dynamic, collaborative, and interactive intelligence among the inspædiers. We will explain in detail and describe the design process and discuss the ultimate design interaction concept & development regarding (almost everything about) simplicity and playfulness of the inspædiers’ experience to transform relevant information (related > meanfull > useful) in productive knowledge (inspiration > insight > foresight) in a very easy and quick way (usability: learnability; understandability; operability; attractiveness...), with a smile in the face (satisfaction) and a wow in the mind (or in the soul).